La Contabilità Analitica per il controllo della gestione nel settore vitivinicolo Atti della Giornata di Studi, Firenze, 3 dicembre 2014 - Enrico Marone (Proceedings e report, 2015)
The volume illustrates the research activity of the UniCeSV Analytical Accounting Observatory presented during the seminar on: La contabilità analitica per il controllo della gestione nel settore vitivinicolo ("Analytical accounting for management control in the wine industry") which was held in Florence on December 3, 2014. On this occasion, some of the studies which UniCeSV has been carrying out in this field in the last years have been presented. During the seminar some results were presented, related to a a sample survey carried out in companies belonging to the denominations Chianti Classico DOCG, Brunello di Montalcino DOCG, Morellino di Scansano DOCG and Monteregio di Massa Marittima DOC. These results have allowed to evaluate the production cost of the single bottle of wine and to determine the standard cost of some reference company typologies.